PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PENGADILAN AGAMA MARTAPURA - Handayani; Ahmad Alim Bachri (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This Research aims to analyze the influence of motivation and discipline of good work simultaneously and partially on the performance of employees in the Religious M artapura. Objects of this study is the Religious Martapura located at Jalan Albasia Banjar Regency. This research is quantitative research that aims to clarify (Explanatory Research) with a saturated sampling techniques in data collection. Data obtained by distributing questionnaires to 44 civil servants at the Religious Martapura, located in Banjar Regency, South Kalimantan. Data were analyzed by multiple regression with SPSS. The results of hypothesis show that the three proposed hypotheses can be accepted, so it can be concluded that the motivation and work discipline significantly affect on employee performance the Religious Courts Martapura either partially or simultaneously